Enraizamiento con ácidos húmicos y extracto de gas en estacas de mora (Rubus glaucus benth) - Álvarez Gavilanes, Félix Adolfo (2013)
This research proposes an analysis has been performed on humic acids and Rooting with seaweed extract stakes Mora (Rubus glaucus Benth) Bio stimulants applied were: humic acid in doses of 1, 1.5 and 2 g. Per liter of water and algae extract of 2, 2.5 and 3 g. Per liter of water. The research work was carried out in the Canton Pelileo Tungurahua Province, in the hamlet Chiquicha, property of Mr. Vinicio Morales. The experimental design was a D.C.A. factorial 3 x 3 with 3 replications and a control with making research data the ANOVA procedure for the analysis of variance test was run for 46 days, to which statistical analysis was used by Infostat was employed Tukey (0.05) . adema an economic analysis for each treatment was used. I consist of application, net income, total income, cost benefit ratio and therefore the cost of production for each plant mulberry. The results determined that the best treatment in the use of the Rooting with humic acid and seaweed extract in stakes Mora (Rubus glaucus Benth) is one treatment (2 g + humic acid extract of seaweed 3 ml). The (humic acid 2 g + 2.5 ml extract of seaweed) T1yT7 is the greatest benefit I present cost 0,42 and the treatment T0 (not aplication) showing the least benefit of 0,20 as it relates to the use of humic acids and rooting algae extract Mora (Rubus glaucus Benth) .